Unusual arachnoid cyst of the quadrigeminal cistern in an adult presenting with apneic spells and normal pressure hydrocephalus - Case report - Topsakal, C; Kaplan, M; Erol, F; Cetin, H; Ozercan, I (Japan Neurosurgical Soc, 2002)
A 67-year-old woman was admitted to our clinic with symptoms of normal pressure hydrocephalus, lower cranial nerve pareses, and pyramidal and cerebellar signs associated with respiratory disturbances. Computed tomography (CT) and magnetic resonance imaging revealed a 4.7 x 5.4 cm quadrigeminal arachnoid cyst causing severe compression of the tectum and entire brain stem, aqueduct, and cerebellum, associated with moderate dilation of the third and lateral ventricles. Emergency surgery was undertaken due to sudden loss of consciousness and impaired breathing. The cyst was totally removed by midline suboccipital craniotomy in the prone position. Postoperatively, her symptoms improved except for the ataxia and impaired breathing. She was monitored cautiously for over 15 days. CT at discharge on the 18th postoperative day revealed decreased cyst size to 3.9 x 4.1 cm. Histological examination confirmed the diagnosis of the arachnoid cyst of the quadrigeminal cistern. The patient died of respiratory problems on the 5th day after discharge. Quadrigeminal arachnoid cysts may compress the brain stem and cause severe respiratory disturbances, which can be fatal due to apneic spells. Patients should be monitored continuously in the preoperative and postoperative period until the restoration of autonomous ventilation is achieved.
Keywords: apneic spells; aqueduct stenosis; arachnoid cyst; hydrocephalus; quadrigeminal cistern